Regional Insurance Markets of the Russian Federation: Development Dynamics in the Post-COVID Period - Belozerov , Sergey A.; Romanova , Anna B. (Economy of Regions, 2024)
The continuing interest in the insurance market of both experts in the field and ordinary citizens who need insurance services highlights the importance of analysing the impact of the COVID-19 pandemic consequences, which significantly affected the activities of insurance market participants in 2021. While the insurance market has largely overcome the negative effects of the pandemic, its consequences still influence the market’s development. The analysis of changes will help develop theoretical and practical recommendations to minimise the consequences of biological threats in the future. The study aims to assess the insurance market in the post-COVID period based on the results of insurers’ activities in 2021 by types of insurance in federal districts of the Russian Federation and to determine development dynamics, the degree of penetration and the need for insurance services in regions. To this end, official statistics were used to examine insurers’ activities by comparing and summarising metadata, considering regional characteristics of the constituent entities of the Russian Federation. It is hypothesised that while emergency conditions affect all sectors of the economy and the social sphere, the insurance market remains stable and quickly adapts to changes. The study concluded that all types of voluntary and compulsory property insurance are presented in the Russian insurance market; in comparison with the pre-COVID period, the insurance sector showed an increase of 17.46 %; a positive trend of increasing fees in almost all regions indicates an increase in the penetration of insurance services. The global events of 2022 have also seriously affected the insurance industry, thus, it can be expected that the insurance sector will undergo a significant transformation in the future.